Comparison of Oral Pregabalin and Intravenous (IV) Lignocaine in Attenuating Stress Response to Endotracheal Intubation in Patients With Hypertension - Noor, Hafiza Maham; Shafaq, Maryam; Imran, Muhammad; Mohyudin, Ammara; Waris, Salman (Biological and Clinical Sciences Research Journal, 2025)
Endotracheal intubation induces a significant stress response, particularly in hypertensive patients, leading to dangerous hemodynamic fluctuations. This study compares the efficacy of oral pregabalin versus intravenous lignocaine in attenuating this response in hypertensive patients scheduled for elective surgeries. Objective: To evaluate and compare the effectiveness of oral pregabalin and intravenous lignocaine in reducing the hemodynamic response to endotracheal intubation in hypertensive patients. Methods: A randomised controlled trial was conducted at the Department of Anaesthesia, Ibn-e-Sina Hospital, Multan, from September 2024 to February 2025. A total of 124 hypertensive patients (ASA II), aged 20–60 years, were randomly assigned into two groups: Group A received 150 mg oral pregabalin one hour before induction, and Group B received 1.5 mg/kg IV lignocaine two minutes before intubation. Hemodynamic parameters, including heart rate, systolic blood pressure, diastolic blood pressure, and mean arterial pressure, were recorded at baseline and 1-minute post-intubation. Data were analysed using SPSS v25.0, with a p-value <0.05 considered statistically significant. Results: Patients in the pregabalin group exhibited significantly lower heart rate, SBP, DBP, and MAP at 1-minute post-intubation compared to the lignocaine group (p<0.05). No severe adverse events were reported in either group, although mild sedation was noted in a few patients in the pregabalin group. Conclusion: Oral pregabalin is more effective than intravenous lignocaine in attenuating the hemodynamic response to intubation in hypertensive patients. Its use as a premedication should be considered in clinical practice, particularly in resource-constrained environments like Pakistan.